Métodos in vitro para controle de qualidade de vacinas clostridiais - Eliane Macedo Sobrinho (2008)
Due to discussions about variability of the results of tests involving animals, and especially due to ethics matter, this study was carried out aiming at assessing and standardizing ELISA test so that it can be used in the quality control of vaccines against enterotoxemia comparing it to serum neutralization test in mice. Experimental vaccines were used; they were evaluated through in vivo method by utilizing serum neutralization test in mice, and in vitro through the use of ELISA test. Immunized rabbit and sheep serum were used along the development of the study. The titration of the epsilon antitoxin was performed from a curve pattern previously established, and the used reactants were properly standardized to an absorbance value around 1, at an espectrofometric range from 0 to 2 at a wavelength 492 nm. The results indicated a lack of correlation (r < 1%) between ELISA and the serum neutralization in mice for a titration of epsilon antitoxin present in the serum of rabbits immunized with polyvalent and monovalent vaccines against Clostridium perfringens type D. Intraplate variation ratio ranged from 1.87 to 4.35% for polyvalent vaccines, and from 0.11 to 6.61% for monovalent vaccines. Intraplaque variation ratios were also little expressive less than2% what indicates high homogeneity of the results. When using sheepserum, the correlation ratio was higher than 99%; this is according to literature review that reports similarity between ELISA and serum neutralization in mice. Inter and intraplate variation ratios were relatively low, varying from 1.35 to 9.961, and from 1.44 to 7.29 respectively. Therefore, it is concluded that the ELISA in vitro method is appropriate and indicated to assess clostridial vaccine potency only when using the percentage of inhibition to calculate the titration degree of epsilon antitoxin in order to reduce discrepancy in the results. Therefore, it may be used by vaccine industries and by regulator agencies as an alternative to serum neutralization tests that determine vaccine potency after it is subjected to an adequate validation process.